Chemical stability and reversibility of PEDOT:PSS electrodes in view of low-cost biocompatible cellulose-assisted biosensors. (June 2021) - Machrafi, H.; Bobinac, I.; Dongo, P.; Gallo, V.; Iermano, F.; Iorio, C.S
Graphical abstract: Abstract: The increasing necessity for small electronics and wireless technologies in energetic devices, such as batteries or supercapacitors and in medical devices, such as sensors, drug delivery systems, calls for new materials, devices and preparation methods. In this work, the possibility of using a PEDOT:PSS hydrogel film as a cathode for a biocompatible cellulose-assisted biosensing device has been explored. The effect of film formulation and preparation method on the electrical conductivity is investigated, i.e. adding a cross-linker and different solvent additives on one side and adding an ionic liquid with and without a metal salt on the other side, for two film thicknesses. The chemical composition of the electrode is studied as a function of the used formulation as well as after being used as cathode in the biosensing device. It appeared that the electrode based on the cross-linker was mechanically robust, but suffered in electrical conductivity, despite the enhancement provided by the solvent additives. The electrode based on the ionic liquid showed a considerable increase in electrical performance, although the mechanical stability was not easy to maintain. The thin film showed a higher electrical conductivity. Although the metal salt enhanced somewhat further the electrical performance, the mechanical one suffered considerably. An application of the PEDOT:PSS electrode as cathode in a biosensing device showed promising results. Concentrations of the order of μl were measured without difficulty and the cathode seemed to be chemically stable and therefore reutilisable, opening future applications in reutilisable low-cost wearable biosensors and corresponding wearable batteries.